ASSESSMENT AND FEEDBACK IN FOREIGN LANGUAGE LEARNING (Ustozlar uchun, 2026)
This article explores the role of assessment and feedback in foreign language learning. It examines different types of assessment, including formative and summative approaches, and highlights their impact on learners’ progress and motivation. The study emphasizes the importance of constructive and timely feedback in enhancing language skills such as speaking, writing, listening, and reading. Furthermore, it discusses modern strategies and tools used in language assessment, including peer assessment and self-assessment. The findings suggest that effective assessment and feedback practices contribute significantly to improving learners’ communicative competence and overall language proficiency.